2021
DOI: 10.1155/2021/3271863
|View full text |Cite
|
Sign up to set email alerts
|

Sports and Health Management Using Big Data Based on Voice Feature Processing and Internet of Things

Abstract: With the support of big data and information technology, various sectors such as sports, health, and medical industry can realize the integration and readjustment of the existing resources, which improve the operation efficiency of the industry and tap its huge potential. With the advancement in big data analysis, voice features, and Internet of Things (IoT), personalized health management is becoming the development trend and breakthrough of sports and health industry. The application of big data will tap out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, researchers found that the school's athletic resources and environment also had a significant effect on adolescents' athletic ability. The literature [15] proposed a method to collect personal exercise data and voice characteristics using IoT devices such as smart bracelets, and to process and analyze these data through big data technology to achieve exercise health management for individuals. The literature [16] focused on comparing the similarities and differences between the concept of health in Olympic sports and the concept of health in Chinese sports culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, researchers found that the school's athletic resources and environment also had a significant effect on adolescents' athletic ability. The literature [15] proposed a method to collect personal exercise data and voice characteristics using IoT devices such as smart bracelets, and to process and analyze these data through big data technology to achieve exercise health management for individuals. The literature [16] focused on comparing the similarities and differences between the concept of health in Olympic sports and the concept of health in Chinese sports culture.…”
Section: Literature Reviewmentioning
confidence: 99%